Serum urate and obstructive sleep apnoea in severe obesity. (August 2015) - Seetho, Ian W; Parker, Robert J; Craig, Sonya; Duffy, Nick; Hardy, Kevin J; Wilding, John PH; Goodson, Nicola J
Obstructive sleep apnoea (OSA) may increase the risk of hyperuricaemia and predispose to gout. The evidence for the effects of OSA on serum urate in severe obesity is limited. This study investigated whether OSA was associated with serum urate in severe obesity and whether continuous positive airway pressure (CPAP) treatment was associated with a fall in urate. Severely obese subjects without known OSA or gout were recruited. Baseline assessments included urate, metabolic parameters, spirometry and overnight polysomnography. OSA patients were initially naive to treatment and were offered CPAP. At follow-up, change in urate was compared between CPAP-treated and non-CPAP-treated subjects. A high urate was defined as greater than the median. Logistic regression was performed to identify associations between (1) OSA and high urate at baseline and (2) use of CPAP and change in urate at follow-up. In total, 92 subjects were recruited (61 (66%) OSA and 31 (34%) non-OSA). Median urate was 345 μmol/L. OSA was associated with high urate in females at baseline after adjusting for confounders (adjusted odds ratio ORadj = 10.2; 95% CI: 1.1, 93.5). At follow-up (14 months), 58 subjects (28 on CPAP and 30 not on CPAP) were reassessed. CPAP was significantly associated with a fall to a low urate category at follow-up ( = 0.017). Regression revealed a trend for a fall in urate category in the CPAP-treated group (ORadj = 9.3; 95% CI: 0.8, 97). Serum urate is associated with OSA in severely obese females and CPAP may reduce levels in patients with OSA. There may be a need to consider and assess for OSA in obese patients with hyperuricaemia and recurrent attacks of gout.